THE RESEARCH ON COOPETITION: TOWARDS A BETTER UNDERSTANDING OF THIS CONSTRUCT AND ITS APPLICATION IN THE TOURISM SECTOR - Chim-Miki, Adriana Fumi (2016)
This paper presents a theoretical review on the coopetition construct, particularly focusing on studies that apply this concept in tourism. The goal is to provide a general overview of this behavior which is source of a new class of advantages: the coopetitive advantage. The research is theoretical. It performed a systematic literature review on coopetition through a bibliometric analysis of the last 20 years of publications in two databases: Scopus and Web of Science. So, the implications of coopetition to tourism, the boundaries of the current use of the construct and the future research on this topic is verified. The result showed that coopetition is seen as an intrinsic behavior of the tourism sector, where firms complement each other to create a market, but simultaneously compete for its division. The existence of a common goal as a developing the tourism destination, is the greatest driver of coopetition, causing the inseparability between cooperation and competition. Thus, coopetition could be a complementary perspective to the competitiveness analysis; however it needs more research, especially to develop explanatory models for tourism destinations.